Influence of selenomethionine and omega-3 fatty acid on serum mineral profile and nutrient utilization of broiler chicken - Kumar, Pankaj (Vet World, 2015)
AIM: This study was conducted to investigate the effect of selenomethionine and omega-3 fatty acid on serum mineral profile and nutrient utilization of broiler chicken. MATERIALS AND METHODS: The present study was a 2×3 factorial arrangement of two levels of selenomethionine (0 and 0.3 ppm) and three levels of omega-3 fatty acid (0, 0.5 and 1%). Day-old Vencobb broiler chicks (n=180), were randomly assigned in six treatment groups. The experiment lasted for 42 days. Treatment groups followed of: Group I was a control. Group II, III, IV, V and VI were supplemented with 0 ppm selenomethionine with 0.5% omega-3 fatty acid, 0 ppm selenomethionine with 1% omega-3 fatty acid, 0.3 ppm selenomethionine with 0% omega-3 fatty acid, 0.3 ppm selenomethionine with 0.5% omega-3 fatty acid and 0.3 ppm selenomethionine with 1% omega-3 fatty acid, respectively. Linseed oil was used as a source of omega-3 fatty acid while sel-plex is used for selenomethionine supplementation. RESULTS: Significant (p<0.05) interaction exist between selenomethionine and omega-3 fatty acid for serum zinc and iron concentration whereas, it was non-significant for serum calcium and copper. Significantly (p<0.05) increased concentration of selenium, zinc, iron and phosphorus was observed in birds fed 0.3 ppm selenomethionine whereas, significantly (p<0.05) increased zinc and iron was observed in birds fed 0.5% omega-3 fatty acid. There was significant (p<0.05) interaction exist between selenomethionine and omega-3 fatty acid for calcium and phosphorus retention percentage. The maximum retention of calcium and phosphorus was recorded in birds supplemented with 0.3 ppm selenomethionine in combination with 0.5% omega-3 fatty acid. There was marked interaction between selenomethionine and omega-3 fatty acid for hemoglobin (Hb), total erythrocytic count, total leukocytic count and platelets (p<0.05) however, it was non-significant for mean corpuscular volume, mean corpuscular Hb, MCH concentration and differential leukocyte count. Dietary selenomethionine significantly (p<0.05) increased the platelet count. Hb concentration was significantly (p<0.05) higher in birds fed 0.5% omega-3 fatty acid whereas, 1% omega-3 fatty acid in the diet drastically increased (p<0.05) the platelet count. CONCLUSION: Supplementation of selenomethionine and omega-3 fatty acid improves the nutrient utilization and mineral retention, which subsequently enhance the bone mineralization. Supplementation also helps in combating the stress.